Shaping Academia for the Public Good : Critical Reflections on the CHSRF/CIHR Chair Program - Potvin, Louise, 1957-; Armstrong, Pat, 1945- (Book collections on Project MUSE., 2013)
Shaping Academia for the Public Good will be a helpful resource for those interested in the potential of new research approaches to improve our healthcare system.